Modelling of a new X-ray backscatter imaging system: simulation investigation - Selvagumar, Senthurran; Yuen, Peter W. T.; Soori, Umair; Piper, Jonathan; James, David; Andre, Daniel; Richardson, Mark A. (IS&T Society for Imaging Science and Technology, 2022)
X-ray backscatter imaging is a powerful technique for medical, aerospace, and security applications. Conventionally, a pinhole is commonly used for focusing x-ray, but there is always a desire to enhance the signal-to-noise-ratio (SNR) and optical throughput compared to a single pinhole. The main aim of this paper is to present a new x-ray backscatter imaging system which was inspired by a Twisted Slit collimator system called the Vortex Collimator and compare the optical throughput and the imaging performance with that of the Twisted Slit' collimator1,2 and the Pinhole imaging systems for axial point sources, where the pinhole system was used purely for comparison purposes. All the comparisons were performed through Ray tracing (Trace-Pro) simulation software. This work shows that the Vortex design yields ~4% higher SNR/optical throughput than that of the Twisted Slit collimator, and ~42.5% higher transmittance. Furthermore, the opening of the Vortex Collimator was increased and reduced to observe the performance, resulting in about ~1% transmittance increment when the opening was increased. Also, thicknesses of the Vortex Collimator and Twisted Slit collimator were increased and reduced and found that reducing the thickness seems to increase the system's throughput marginally.
Keywords: Coded aperture; Vortex Collimator; X-ray Backscatter; Twisted Slit collimator